Algoritma Neural Network Menggunakan Model Particle Swarm Optimization Untuk Prediksi Penyakit Kanker Payudara - Marsiska Ariesta Putri; Iwan Setiawan Wibsiono (Universitas Ngudi Waluyo, 2022)
ABSTRACT Breast cancer is one of the causes of cancer deaths in women worldwide. One technique to diagnose breast cancer: mammography. In this study developed a system to classify the